Evaluation of pharmacological interactions after administration of a levamisole, albendazole and ivermectin triple combination in lambs - Suárez, Gonzalo (2013)
The goals of the current trial were (a) to characterize the plasma disposition kinetics of levamisole (LEV), albendazole (ABZ) and ivermectin (IVM), each administered either alone (single active ingredient) or as a combined formulation to lambs; (b) to compare the clinical anthelmintic efficacy of the same drugs given either separately or co-administered to lambs infected with resistant nematodes. Fifty Corriedale lambs naturally infected with multiple resistant gastrointestinal nematodes were involved in the following experimental trials: (a) “Pharmacokinetic trial”: the animals were allocated into five groups (n = 10 each) and intraruminally treated with either LEV (8 mg/kg), ABZ (5 mg/kg), IVM (0.2 mg/kg), or with a LEV + ABZ + IVM combined formulation, where each active ingredient was administered at the same dose. Blood samples were collected over 15 days post-treatment and drug plasma concentrations measured by HPLC. (b) “Efficacy trial”: the same treated groups plus an untreated control group were used to assess the comparative anthelmintic efficacy by the faecal egg count reduction test (FECRT). Although the overall LEV disposition kinetics was unaffected, significantly lower (61%) ABZ-sulphoxide and higher (71%) IVM systemic availabilities were obtained after administration of the combined formulation in comparison to those obtained after treatment with each drug alone. A multiple drug resistance situation was observed for Haemonchus spp. The observed efficacies were 52% (LEV), 72% (ABZ), 80% (IVM) and 87% (triple combined formulation). The results reported here contribute to the pharmaco-therapeutic knowledge on drug combinations. This type of research is crucial before further development of combined anthelmintic preparations reaches the market to deal with resistant nematode control. The co-administration of LEV + ABZ + IVM did not result in a significant advantageous anthelmintic effect compared to the treatment with IVM alone. The simultaneous/combined administration of LEV, ABZ and IVM may account for a drug–drug pharmacological interaction in infected lambs. The pharmacokinetic interaction accounted for a reduced ABZ-sulphoxide and enhanced IVM systemic exposure following the combined treatment.